Studies of Health Effects from Nuclear Testing near the Semipalatinsk Nuclear Test Site, Kazakhstan - Bernd Grosche; Tamara Zhunussova; Kazbek Apsalikov; Ausrele Kesminiene (University Library System, University of Pittsburgh, 2015)
The nuclear bomb testing conducted at the Semipalatinsk nuclear test site in Kazakhstan is of great importance for today's radiation protection research, particularly in the area of low dose exposures. This type of radiation is of particular interest due to the lack of research in this field and how it impacts population health. In order to understand the possible health effects of nuclear bomb testing, it is important to determine what studies have been conducted on the effects of low dose exposure and dosimetry, and evaluate new epidemiologic data and biological material collected from populations living in proximity to the test site. With time, new epidemiological data has been made available, and it is possible that these data may be linked to biological samples. Next to linking existing and newly available data to examine health effects, the existing dosimetry system needs to be expanded and further developed to include residential areas, which have not yet been taken into account. The aim of this paper is to provide an overview of previous studies evaluating the health effects of nuclear testing, including some information on dosimetry efforts, and pointing out directions for future epidemiologic studies.